A Comparative Study of Interdigitated Electrode and Quartz Crystal Microbalance Transduction Techniques for Metal–Organic Framework-Based Acetone Sensors - Chappanda, Karumbaiah N.; Tchalala, Mohamed R.; Shekhah, Osama; Surya, Sandeep G.; Eddaoudi, Mohamed; Salama, Khaled N. (Sensors (Basel, Switzerland), 2018)
We present a comparative study of two types of sensor with different transduction techniques but coated with the same sensing material to determine the effect of the transduction mechanism on the sensing performance of sensing a target analyte. For this purpose, interdigitated electrode (IDE)-based capacitors and quartz crystal microbalance (QCM)-based resonators were coated with a zeolitic–imidazolate framework (ZIF-8) metal–organic framework thin films as the sensing material and applied to the sensing of the volatile organic compound acetone. Cyclic immersion in methanolic precursor solutions technique was used for depositing the ZIF-8 thin films. The sensors were exposed to various acetone concentrations ranging from 5.3 to 26.5 vol % in N2 and characterized/compared for their sensitivity, hysteresis, long-term and short-term stability, selectivity, detection limit, and effect of temperature. Furthermore, the IDE substrates were used for resistive transduction and compared using capacitive transduction.